PROSES PELAKSANAAN PROGRAM SOCIAL TRUST FUND (STF) DOMPET DHUAFA BAGI KORBAN GEMPA DI LUBUK ALUNG PADANG PARIAMAN - Musfi Yendra (Ensiklopedia of Journal, 2019)
The most crucial issue regarding regional autonomy is poverty. Poverty has become sensitive topic to be talked about. The released statistic number of poor citizens will always be associated with the performance of government. The decreasement of it consindered as an achievement, thus no regional government want the amount of poor citizen increase. Eradicating poverty by showing decreasement in the amount of poor citizens anually are stated as national consensuss by the center government. One situation that can't never be predicted by government is natural disaster. Recently some of regions in Indonesia are highly susceptible to natural disasters. Natural disaster is one of the main cause of temporary poverty. Governmet efforts in decreasing the number of poor citizens are always threatened by natural disaster, morever if it happened in big scale. The damage that cause by natural disaster destroy any resources and efforts of eradicating poverty by the government. Non Government Organization (NGO) exist to help government in facing the impact of natural disaster. Dompet Dhuafa is one of the NGO that help government of Padang Pariaman when earthquake happened at 30th September 2009, by establishing economicempowerment program called Social Trust Fund (STF). The purpouse of this research is to described the process of the implemantation of STF to the victim of earthquake who treathened to be poor. Using qualitative method the research is carried at Dompet Dhuafa unit office of STF economic empowerment program at Lubuk alung, Padang Pariaman. The research found a fact that the victim of the earthquake are not only physically and psycologycally suffered, but also threatened to be on poverty. Loosing their jobs and ecomomical resources are also unavoidable. Meanwhile government only focused on fixing public facilities and infrastructure, missed to allocate budget to help funding citizen. Using qardhul hasan system in empowering, STF proved to be able to help the citizen to rebuild their economic resourcess. The process of the implementation of this program consist of three steps; establishing, operating and asset reform. The research suggest that in the future government should allocate budget to help funding the citizen, especially to those in the regions that highly susceptible to natural disaster. Involvement of NGO in handling the impact of natural disaster is essensial to be on long term.